A Review of Three Decades of Research Dedicated to Making Equine Bones Stronger: Implications for Horses and Humans - Brian D. Nielsen (Animals, 2023)
Much research has been conducted in an attempt to decrease skeletal injuries in athletic horses. The objective of this literature review is to compile the findings of over three decades of research in this area, make practical recommendations, and describe how research can develop over the years. An initial study investigating the role of bioavailable silicon in the diets of horses in race training produced the unexpected finding of decreased bone mineral content of the third metacarpus subsequent to the onset of training. Further studies revealed this decrease to be associated with stall housing eliminating high-speed exercise, leading to disuse osteopenia. Only relatively short sprints (between 50 and 82 m) were necessary to maintain bone strength and as few as one sprint per week provided the needed stimuli. Endurance exercise without speed fails to elicit the same benefits to bone. Proper nutrition is also required for optimal bone health, but without the right exercise, strong bone cannot be maintained. Several pharmaceuticals may have unintended consequences capable of impairing bone health. Many of the factors influencing bone health in horses also exist in humans including a sedentary lifestyle, improper nutrition, and pharmaceutical side-effects.